Peranan Faktor-Faktor Individual Dalam Mengembangkan Usaha Studi Kuantitatif Pada Wirausaha Kecil Di Salatiga - Komala Inggarwati; Arnold Kaudin (Universitas Prasetiya Mulya, 2010)
The enormous number of micro enterprises contributes relatively low to the aggregate economy. This is due to the fact that many small businesses do not grow although it has been run for years. Reluctance to grow may be due to, for instance, the desire to retain ownership or avoidance of loss of satisfaction. This study aims to examine the infuence of several individual factors that may afect growth intention. Those factors are the start-up motivation, self-efcacy and risk taking propensity of the business owners. The sample of this study were 50 pedagang kreatif lapangan in Salatiga who are the founder of his/her business. Multiple-regression analyses reveal that start-up motivation and self-efcacy signifcantly afect growth intention. This means that entrepreneurs who start their business because of some positive reasons and faith have greater intention to grow. The result also indicates that although a micro-entrepreneur has a high degree of risk taking propensity, his/her intention to grow may be low when he/she lacks of neither positive start-up motivation nor a high.